Activation of the PhoPR-Mediated Response to Phosphate Limitation Is Regulated by Wall Teichoic Acid Metabolism in Bacillus subtilis - Devine, Kevin M. (Frontiers in Microbiology, 2018)
Phosphorous is essential for cell viability. To ensure an adequate supply under phosphate limiting conditions, bacteria induce a cohort of enzymes that scavenge for phosphate, and a high affinity transporter for its uptake into the cell. This response is controlled by a two-component signal transduction system named PhoBR in Escherichia coli and PhoPR in Bacillus subtilis. PhoR is a sensor kinase whose activity is responsive to phosphate availability. Under phosphate limiting conditions, PhoR exists in kinase mode that phosphorylates its cognate response regulator (PhoB, PhoP). When activated, PhoB~P /PhoP~P execute changes in gene expression that adapt cells to the phosphate limited state. Under phosphate replete conditions, PhoR exists in phosphatase mode that maintains PhoB/PhoP in an inactive, non-phosphorylated state. The mechanism by which phosphate availability is sensed and how it controls the balance between PhoR kinase and phosphatase activities has been studied in E. coli and B. subtilis. Two different mechanisms have emerged. In the most common mechanism, PhoR activity is responsive to phosphate transport through a PstSCAB/PhoU signalling complex that relays the conformational status of the transporter to PhoR. In the second mechanism currently confined to B. subtilis, PhoR activity is responsive to wall teichoic acid metabolism whereby biosynthetic intermediates can promote or inhibit PhoR autokinase activity. Variations of both mechanisms are found among bacteria that allowing each to adapt to phosphate availability in their particular environmental niche.